Musical chinoiserie - Kang, Angela (2012)
Chinoiserie remains relatively unexplored in the context of music and is usually isolated as a mid-eighteenth-century phenomenon characterized by the use of decorative Chinese motifs and concepts in Western art, porcelain, furniture, and architecture. This thesis enriches possible readings of musical chinoiserie by exploring its relationship to the intense fashion for Chinese commodities, its correlation to particular social and political climates, and its connection to the eternal themes of the feminine and utopian pastoral. As a recurring and evolving phenomenon, chinoiserie has been manifested across the past three centuries in various genres and works central to Western music. The following chapters provide case studies which draw attention to particularly rich constellations of ideas about chinoiserie, and analyse the various ways that 'the West' has confronted, represented, and appropriated Chinese difference in music. Chapter two examines the emergence of eighteenth-century European music theatre/ drama inspired by China and its interrelation with royalty and nobility, consumer goods, fashion, and aesthetic sensibility. Chapter three explores early twentieth-century French musical works by Debussy, De Falla, and Roussel, which are inspired by nostalgic and utopian Chinese landscapes. In chapter four, the music of Mahler, Puccini, and Stravinsky reveal alternative fin de siècle approaches to chinoiserie. Common themes include an increased interest in authenticity; overt and subsumed Chinese elements; and the integration of chinoiserie into existing programmes. As a counterpoint to this, chapter five turns to popular music genres which directly responded to the social and political reality of Chinese immigration to America. The straightforward, formulaic, and market driven style of Tin Pan Alley songs provides the most explicit examples of musical chinoiserie, which upon examination reveal a variety of hidden beliefs, prejudices, aspirations and idealized visions of China. By no means are these chapters intended to offer a comprehensive survey of musical chinoiserie, but they provide case studies which demonstrate the ways in which a musical work can interact with a multiplicity of intellectual and emotional responses to the West's encounter with China during important social, political, and historical events.